2023
DOI: 10.3390/life13051079
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evaluation after Transcatheter Aortic Valve Implantation: A Comprehensive Review

Abstract: Transcatheter aortic valve implantation (TAVI) is an increasingly popular treatment option for patients with severe aortic stenosis. Recent advancements in technology and imaging tools have significantly contributed to the success of TAVI procedures. Echocardiography plays a pivotal role in the evaluation of TAVI patients, both before and after the procedure. This review aims to provide an overview of the most recent technical advancements in echocardiography and their use in the follow-up of TAVI patients. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 88 publications
0
1
0
Order By: Relevance
“…People who have the EuroScore II from 4 to 8 may receive either SAVR or TAVI [ 4 ]. Echocardiography assessment of this group of patients after either SAVR or TAVI is crucial in terms of reverse myocardial remodeling, valve-related complications, such as bacterial endocarditis, aortic valve regurgitation or paravalvular leakage as well as mitral valve regurgitation, all of which influence the rate of survival [ 20 ]. These data could be used as evidence in the decision-making process for better treatment options of severe aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…People who have the EuroScore II from 4 to 8 may receive either SAVR or TAVI [ 4 ]. Echocardiography assessment of this group of patients after either SAVR or TAVI is crucial in terms of reverse myocardial remodeling, valve-related complications, such as bacterial endocarditis, aortic valve regurgitation or paravalvular leakage as well as mitral valve regurgitation, all of which influence the rate of survival [ 20 ]. These data could be used as evidence in the decision-making process for better treatment options of severe aortic stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] In addition, due to the reduction of afterload after valve intervention, myocardial wall stress decreases and diastolic subendocardial perfusion enhances, leading to a better longitudinal myocardial function. 4 Oslo University Hospital, Rikshospitalet, is a tertiary center and we conduct approximately 500 TAVI procedures annually. Our research group showed recently that left ventricular mechanical dispersion by Speckle Tracking Echocardiography (STE) was useful for predicting pacemaker implantation after TAVI.…”
mentioning
confidence: 99%